MENGURANGI GANGGUAN KEDIP TEGANGAN PADA PERALATAN INDUSTRI - Rafael Sianipar (Website, 2016)
Voltage flicker disturbance is one form of power quality disturbances that are considered most likely to cause losses due to the disruption of the operation of various processes in the industry, especially industries using control equipment, modern power electronics and data processing, which are generally very sensitive to voltage variations. Losses incurred as a result of the disorder is relatively large, including the form of damage to the product, damage to the means of production and cessation of production. This disorder usually caused by the occurrence of the interference of the transmission and distribution networks, as well as the installation of the consumer or industry itself. Therefore, the discussion and understanding of the characteristics of voltage flicker disturbances and sensitivity of industrial equipment for the disorder, which is the issue of this writing, expected to be useful in determining the electrical power quality criteria can be agreed well by the corporate who manage the electricity in Indonesia and industrial or manufacturing as the users.Gangguan kedip tegangan adalah salah satu bentuk gangguan kualitas tenaga listrik yang dianggap paling sering menyebabkan kerugian akibat terganggunya pengoperasian berbagai proses di industri, khususnya industri yang menggunakan peralatan kontrol, elektronika daya modern dan pengolahan data, yang umumnya sangat sensitif terhadap variasi tegangan. Kerugian yang timbul akibat gangguan tersebut relatif cukup besar, diantaranya berupa kerusakan produk, kerusakan alat-alat produksi bahkan terhentinya produksi. Gangguan ini umumnya disebabkan oleh terjadinya gangguan pada jaringan transmisi dan distribusi, maupun pada instalasi dari konsumen atau industri itu sendiri. Oleh karenanya, pembahasan dan pemahaman tentang karateristik gangguan kedip tegangan dan sensitivitas peralatan industri terhadap gangguan tersebut, yang merupakan inti dari penulisan ini, diharapkan dapat bermanfaat dalam menentukan kriteria kualitas tenaga listrik yang dapat disepakati baik oleh pengelola kelistrikan di Indonesia, maupun industri atau pabrikan sebagai pengguna tenaga listrik tersebut.